Consider the master-slave game model of integrated energy system with step carbon trading and demand response - Zhang, Yi; Zhang, Zhezhou (Frontiers in Energy Research, 2025)
In the context of deepening energy coupling and the high penetration of renewable energy, this paper proposes a master-slave game model incorporating comprehensive demand response and a stepped carbon trading mechanism. The goal is to optimize scheduling of demand response resources and fully leverage the flexibility of energy use within an integrated energy system while addressing conflicts of interest among multiple stakeholders, thereby enhancing trading revenue in Energy Markets while considering lower carbon emissions. Firstly, the basic structure of the integrated energy system is analyzed, and the decision-making entities are modeled. A stepped carbon pricing mechanism is introduced to constrain the carbon emissions of each entity, while comprehensive demand response is introduced on the user side to improve user economic benefits and energy use comfort. Secondly, an energy manager is designated as the leader, while energy suppliers, energy storage operators, and users act as followers, forming a master-slave game model to explore the interaction mechanisms among the entities. Finally, the model is solved using the differential evolution algorithm and the Cplex tool on the Matlab platform, resulting in an equilibrium solution. A case study is conducted using relevant data from a typical region in China, demonstrating that the scheduling of demand response resources are improved, and carbon emissions are reduced, thereby verifying the rationality and effectiveness of the proposed model. Profits of EMO, EGO, ESO and users have respectively increased 34%, 46%, 31% and 7%. The carbon emissions of the system have decreased 11%.